THE EFFECT OF PLAYING WITH LOOSE PARTS ON FINE MOTOR DEVELOPMENT IN PRESCHOOL CHILDREN AT THE KUNCI III YOGYAKARTA - Istichomah; Setyo Retno Wulandari; freasy kora (Holistic Nursing Plus, 2026)
Background: In order to move items, doodle, arrange blocks, cut, and write, people must develop their fine motor skills, which are small muscles like fingers and hands that require dexterity and hand-eye coordination. A game called "Loose Part Play" makes use of loose elements that can be moved, mixed, carried, redesigned, separated, and reassembled. According to the World Health Organization (WHO, 2021), fine motor development impairments affect 5–10% of preschool-aged children. Purpose: for the measurement of the effect of the treatment by comparing the posttest scores with the pretest scores. Methods: This study is a quantitative pre-experimental design employing a pretest-posttest group. The population includes 73 children at the health center, with random sampling being the chosen technique. The sample comprises 19 preschool children from the Key III Posyandu. The instrument utilized for data collection in this study was an observation sheet. Univariate data analysis was conducted to determine the frequency distribution using percentages, while bivariate analysis was performed using the Wilcoxon test in SPSS. Results: Prior to the intervention, 100% of the children exhibited fine motor development scores within the "Beginning to Develop" category. Following the intervention, 1% of the children remained in the "Beginning to Develop" category, while 95% transitioned to the "Developing as Expected" category. Conclusions: Before the intervention, the children's fine motor development was categorized as "Beginning to Develop." After the intervention, their fine motor development was categorized as "Developing as Expected." Keywords: Fine Motor Development, Preschool, Children